Pengungkapan Informasi Keuangan Secara Sukarela di Internet oleh Perusahaan Besar di Indonesia - Ernawati Ernawati; Hasya Fayiatha (Global Financial Accounting Journal, 2019)
The purpose of this study is to examine the impact of characteristics as a potential factor that might influence each financial disclosure on the internet voluntarily by large companies in Indonesia. The characteristic in this study are the company size, leverage, profitability, company age, dispersion ownership, industrial sector, and auditor type. The sample chosen uses a purposive sampling method to collect as many as 414 large companies listed on the Indonesia Stock Exchange in 2013 to 2017. Using binary logistic regression to determine the effect of independent variables on the dependent variables and processed using the program of SPSS version 21. The results of data analysis and conclusions indicate that the size of the company has a significantly positive effect on Internet Financial Reporting. Variables of company age, industry sector, and auditor type indicate a significantly negative influence. Wheares, for the variables of leverage, profitability, and dispersion of ownership there are no significant findings on Internet Financial Reporting.